Aubrieta birolmutlui (Brassicaceae), a new species from Eastern Turkey with molecular phylogenetic support - Dönmez Ali̇ A.; Aydin, Zübeyde Uğurlu; Kaya Yasi̇n; Yüzbaşioğlu İ. Sirri (Phytotaxa, 2023)
Aubrieta birolmutlui is described as a new species from the eastern part of Turkey based on morphological and molecular data. The new species is confined to limestone rock and is most similar to A. macrostyla, but it differs by having only rosette-like basal leaves, larger and entire leaves with sparse indumentum, bigger fruit and short style. The new species is also close to A. libanotica and A. canescens according to the morphological data. The morphological characters of the new species distinguishing it from its relatives are given in a comparative table and discussed. This new species, the closest relative taxa, and some of the Aubrieta species have been studied by sequencing the most commonly used plastid markers in the genus, namely trnS- ycf9, trnL-F and trnL intron. All the sequences have been evaluated by Maximum Likelihood and Bayesian approaches and the results support the morphological species delimitation. A detailed morphological description, photographs from the habitat of the new species, and a phylogenetic consensus tree are provided herein. The new species is assigned to the CR threat category of the IUCN.